Climate corridors for strategic adaptation planning. Issue 6 (20th November 2017) - Orlowsky, Boris; Calanca, Pierluigi; Ali, Irshad; Ali, Jawad; Elguera Hilares, Agustin; Huggel, Christian; Khan, Inamullah; Neukom, Raphael; Nizami, Arjumand; Qazi, Muhammad Abbas; Robledo, Carmenza; Rohrer, Mario; et al.
Abstract : Purpose: Although the importance of climate change is generally acknowledged, its impacts are often not taken into account explicitly when planning development projects. This being due to limited resources, among others, this paper aims to propose a simple and low-cost approach to assess the viability of human activities under climate change. Design/methodology/approach: Many human activities are feasible only within a narrow range of climatic conditions. Comparing such "climate corridors" with future climate projections provides an intuitive yet quantitative means for assessing needs for, and the viability of, adaptation activities under climate change. Findings: The approach was tested within development projects in Pakistan, Peru and Tajikistan. The approach was shown to work well for forestry and agriculture, indicating positive/negative prospects for wheat in two districts in Pakistan, temperature constraints for maize in Peru and widening elevation ranges for walnut trees in Tajikistan. Practical implications: Climate corridor analyses feed into the preparation of Local Adaptation Plans of Action in Pakistan. Originality/value: The simplicity and robustness of climate corridor analysis allow for efficient analysis and communication of climate change impacts. It works when data availability is limited, but it can as well accommodate a wide range of complexities. It has proven to be an effective vehicle for mainstreaming climate change into adaptation planning.